Characterization of rhizoctonia isolates and effects of silicon and planting distance on rice sheath blight disease management - Ei, Ei Khaing (2015)
Sheath blight caused by the fungus Rhizoctonia solani Kuhn (Teleomorph: Thanatephorus cucumeris (A.B.Frank) Donk has become an economically important disease of rice in tropical Asia, especially in intensive rice cropping systems and high nitrogen fertilizer applications. To sustain high yield, more nitrogen fertilizer input is needed and this will increase disease incidence. However, in modern agricultural practices it is highly important to manage diseases and pests using efficient methods with minimum harm to the environment. Although silicon has been reported to significantly reduce fungal diseases in crops and planting density is an important factor influencing yield of rice and disease development, this is not the practice adopted in Malaysia. This study focused on characterization of Rhizoctonia isolates in major rice growing areas and to evaluate the effect of silicon (Si), copper (Cu) and zinc (Zn) applications on MR219 and MR 253 cultivars and to investigate the effect of Si and spacing on sheath blight severity and yield improvement. A total of 16 isolates of Rhizoctonia were collected from various states in Peninsula Malaysia and studied for their morphological and molecular characteristics as well as test for pathogenicity. Colony growth rate were not significantly different among isolates but sclerotial features were varied among isolates. All 16 isolates were identified as Rhizoctonia solani through a Basic Local Alignment Search Tool (BLAST) search (with similarity ranging from 96 to 100%). Kelantan isolate (R12) was more virulent than all other isolates. Silicon treatment (24 g kg-1 soil) was found to significantly reduce disease severity by 17.16% for cultivar MR219 and 29.04% for MR253 compared to the respective control treatments. Si rate gave a yield of 56.2 g pot-1 for cultivar MR 219 and 27.56 g pot-1 for MR253 which were both significantly higher than the control of 30.09 g pot-1 for cultivar MR219 and 16.10 g pot-1 for MR253 respectively. Silicon treatment showed significantly higher lignin content of 6.62% in cultivar MR219, and 5.09% in MR253 compared to the two controls of the same cultivars of 3.60% and 3.33% respectively. These were also significantly higher compared to Cu and Zn treatments. From the results of the first experiment, Si treatment and MR219 cultivar giving the lowest sheath blight disease severity (30.49%) and improved yield were selected for study in a second glasshouse experiment. Analysis of data showed significant difference for disease incidence and disease severity were higher for 20 cm x 15 cm compared 25 cm x 25 cm spacing with or without application of Si. In the absence of disease, Si increased grain yield by 190.32 g pot-1 and 215.36 g pot-1 respectively for 25 x 25 cm and 20 x 15 cm spacing compared to the control of 145.61 g pot-1 and 153.24 g pot-1 respectively. However, in the presence of sheath blight disease, Si treatment gave a 48% and 90 % higher mean grain yield respectively for 25 x 25 cm and 20 x 15 cm spacing compared to the controls. Chitinase and β-1, 3 glucanase were induced in Si treated plants with increasing time after inoculation. The highest level of chitinase and β-1,3 -glucanase expression was recorded at two and four days after inoculation, respectively. This study showed the potential contribution for reducing sheath blight disease through manipulation of spacing (25 cm x 25 cm) and rice grain yield improvement via Si application.